Formulasi Hair Tonic dari Ekstrak Etanol, Fraksi Etanol, dan Fraksi Kloroform-Metanol Kayu Secang (Caesalpinia sappan L.) - Dina Yuspita Sari; Ratna Widyasari; Weni Puspita (Jurnal Farmasi Indonesia, 2021)
Secang wood (Caesalpinia sappan L.) has been used as an antioxidant in cosmetic products. The bioactive compound contained in secang wood are brazilin, brazilein, 3´-O-methylbrazilin, sappanone, chalcone, and sappankalkon as secondary metabolite components. This study aims to formulating hair tonic from extracts and fractions of secang wood and to determine the quality of hair tonic formulas using ethanol extract (Eet), ethanol fraction (Fen), and chloroform-methanol fraction (Fkm) of secang wood. The extraction process was carried out using maceration with 96% ethanol as ellent, after that extact partitioned using n-hexane. Fen was then applied using vacuum column chromatography using chloroform, chloroform: methanol (5:1), and methanol as eluent. Eet, Fen, and Fkm of secang wood were then formulated. Hair tonic evaluation includes organoleptic test, determination of pH value, viscosity determination, homogeneity test, and hair growth activity. The results showed that the three hair tonic formulas produced red-orange color, smelled aromatic in solution form, had a pH of 7, were homogeneous, had a viscosity of 3 cps, and showed activity on hair growth and hair weight of rabbits. FIII gave significantly different results from negative control (p <0.05) on rabbit hair length data on day 30, so ii can be concluded that FIII shows the best activity. All three formulas were qualify according to standard requirements and has activity on hair growth.